Balance Control is Sequentially Correlated with Proprioception, Joint Range of Motion, Strength, Pain, and Plantar Tactile Sensation Among Older Adults with Knee Osteoarthritis - Peixin Shen; Simin Li; Li Li; Daniel T. P. Fong; Dewei Mao; Qipeng Song (SpringerOpen, 2024)
Abstract Background Patients with knee osteoarthritis (KOA) are at high risk for falls, which is attributed to their impaired balance control. Identifying factors associated with balance control facilitates the development of precise KOA rehabilitation programs. This study was to investigate the correlations of balance control with proprioception, plantar tactile sensation (PTS), pain, joint range of motion (ROM), and strength among older adults with and without KOA, as well as the magnitudes and sequence of correlation of these factors to balance control. Methods A total of 240 older adults with (n = 124, female: 84, age: 68.8 ± 4.0 years) and without (n = 116, female: 64, age: 67.9 ± 3.5 years) KOA were recruited and assigned to the KOA and control groups. Their proprioception, PTS, pain, ROM, and strength were measured. Pearson or Spearman correlations were used to test whether they were significantly related to their Berg Balance Scale (BBS), and factor analysis and multivariate linear regression were used to determine the degrees of correlation between each factor and the BBS. Results Compared to the control group, the KOA group had lower BBS score, larger proprioception and PTS thresholds, smaller ROM, and less strength (p: 0.008, < 0.001-0.016, < 0.001-0.005, < 0.001-0.014, and < 0.001-0.002, respectively). In the KOA group, the BBS was weakly to moderately correlated with proprioception, PTS, pain, ROM, and strength (r: 0.332-0.501, 0.197-0.291, 0.340, 0.212-0.508, and 0.236-0.336, respectively). While in the control group, the BBS was correlated with proprioception and strength (r: 0.207-0.379, and 0.212-0.410). In the KOA group, BBS = 54.41+ (0.668*strength) - (0.579*PTS) - (1.141*proprioception) + (1.054* ROM) - (0.339*pain). While in the control group, BBS = 53.85+ (0.441*strength) - (0.677*proprioception). Conclusion Worse proprioception and PTS, smaller ROM, and less strength were detected among older adults with KOA, and their proprioception, PTS, pain, ROM, and strength were all related to balance control. Proprioception had the strongest correlations, followed by ROM, strength, pain, and PTS. Precise KOA rehabilitation programs may be proposed following the sequence of improving the five factors.